Contextualizing Chinese globalization - Schortgen, Francis (Henry Stewart Talks, 2013)
China, Business globalization, Geopolitics, Geoeconomics, Geostrategy, Contextualization, Peaceful/unpeaceful rise, Home country motivations, Target country perceptions